Focal Thyroid Incidentalomas on 18F-FDG PET/CT: A Systematic Review and Meta-Analysis on Prevalence, Risk of Malignancy and Inconclusive Fine Needle Aspiration - de Leijer, J. F.; Metman, M. J. H.; van der Hoorn, A.; Brouwers, A. H.; Kruijff, S.; van Hemel, B. M.; Links, T. P.; Westerlaan, H. E. (Frontiers in Endocrinology, 2021)
Background The rising demand for 18F-fluorodeoxyglucose positron emission tomography with computed tomography (18F-FDG PET/CT) has led to an increase of thyroid incidentalomas. Current guidelines are restricted in giving options to tailor diagnostics and to suit the individual patient. Objectives We aimed at exploring the extent of potential overdiagnostics by performing a systematic review and meta-analysis of the literature on the prevalence, the risk of malignancy (ROM) and the risk of inconclusive FNAC (ROIF) of focal thyroid incidentalomas (FTI) on 18F-FDG PET/CT. Data sources A literature search in MEDLINE, Embase and Web of Science was performed to identify relevant studies. Study selection Studies providing information on the prevalence and/or ROM of FTI on 18F-FDG PET/CT in patients with no prior history of thyroid disease were selected by two authors independently. Sixty-one studies met the inclusion criteria. Data analysis A random effects meta-analysis on prevalence, ROM and ROIF with 95% confidence intervals (CIs) was performed. Heterogeneity and publication bias were tested. Risk of bias was assessed using the quality assessment of diagnostic accuracy studies (QUADAS-2) tool. Data synthesis Fifty studies were suitable for prevalence analysis. In total, 12,943 FTI were identified in 640,616 patients. The pooled prevalence was 2.22% (95% CI = 1.90% - 2.54%, I2 = 99%). 5151 FTI had cyto- or histopathology results available. The pooled ROM was 30.8% (95% CI = 28.1% - 33.4%, I2 = 57%). 1308 (83%) of malignant nodules were papillary thyroid carcinoma (PTC). The pooled ROIF was 20.8% (95% CI = 13.7% - 27.9%, I2 = 92%). Limitations The main limitations were the low to moderate methodological quality of the studies and the moderate to high heterogeneity of the results. Conclusion FTI are a common finding on 18F-FDG PET/CTs. Nodules are malignant in approximately one third of the cases, with the majority being PTC. Cytology results are non-diagnostic or indeterminate in one fifth of FNACs. These findings reveal the potential risk of overdiagnostics of FTI and emphasize that the workup of FTI should be performed within the context of the patient's disease and that guidelines should adopt this patient tailored approach.